Productivity Losses Due to Migraine in Slovenia: An Analysis of Absenteeism and Presenteeism Costs Based on Administrative and Self-Reported Data - Lotrič Dolinar Aleša; Žvan Bojana; Došenović Bonča Petra (Sciendo, 2020)
Migraine is associated with significant morbidity and a significantly negative impact on the quality of life. A better understanding of the economic impact of migraine is becoming increasingly important. This paper aims to shed light on absenteeism and presenteeism costs of migraine in Slovenia.